2014
DOI: 10.1186/1752-4458-8-18
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and psychiatric care in Bolivia: what do we know?

Abstract: BackgroundRecently Bolivia has implemented a universal health system, but their mental health policy is still emerging.ObjectivesTo investigate the current state of the mental health care system in Bolivia and discuss challenges for structuring a coordinated network of services that can effectively meet the needs of the Bolivian population.MethodsThis review was conducted by searching for scholarly articles through the databases Lilacs, Medline OPS, HISA and IBECS REPIDISCA via the search portal in the Virtual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
(18 reference statements)
0
11
0
Order By: Relevance
“…Even when insurance is available, supply and infrastructure constraints limit healthcare access (36, 37). Bolivia has 1.2 doctors and 2.1 nurses per 1000 inhabitants (36), and of the 2875 primary care centers, 45% do not have a physician (2007 data) (35). …”
Section: Introductionmentioning
confidence: 99%
“…Even when insurance is available, supply and infrastructure constraints limit healthcare access (36, 37). Bolivia has 1.2 doctors and 2.1 nurses per 1000 inhabitants (36), and of the 2875 primary care centers, 45% do not have a physician (2007 data) (35). …”
Section: Introductionmentioning
confidence: 99%
“…Jaen-Varas et al (2014) found a similar profile in a review of mental health services in Bolivia. Although a universal health care system has been in place since 2007, 77% of the population has been excluded from access to it due to economic, social, geographical and cultural barriers.…”
mentioning
confidence: 65%
“…However, in recent years, mental health care has received increased attention from the Bolivian government including the implementation of a national plan ( Plan Nacional de Salud Mental 2009–2015), the goal of which is to increase prevention, early detection, and timely treatment of psychological, neurological, and substance use disorders [ 12 ]. SAFCI ( Salud Familiar Comunitaria Intercultural , or Program for Intercultural Family Health Care in the Community) is the major program for providing primary care throughout the country, and includes mental health promotion in its scope [ 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, however, the health system in Bolivia, as in other LMICs, lacks the human resources needed to provide adequate care, including monitoring and self-management support, to patients with depression in primary care settings [ 12 , 14 ]. Mobile health (mHealth) tools may help fill this gap, yet mHealth solutions have been largely overlooked in efforts to improve the reach of mental health care in poorer countries [ 15 ].…”
Section: Introductionmentioning
confidence: 99%